Liquid Biopsies in Ewing Sarcoma - Krumbholz, Manuela; Metzler, Markus (Ewing Sarcoma, 2021)
Liquid biopsies enable noninvasive therapy monitoring in patients with solid tumors. Specific serum markers such as proteins, hormones, or enzymes released from tumor cells or in response to tumor growth can be used for quantification of the tumor burden. However, only a fraction of pediatric tumors has none of these serum markers, but tumor-specific genetic alterations represent reliable alternatives. Here we describe a method for using genomic fusion sequences as liquid biopsy markers in Ewing sarcoma patients.
CRIS-Team Scopus Importer:2021-01-01
Keywords: Cell-free circulating DNA; Double-quenched probes; Droplet digital PCR; Ewing sarcoma; Genomic fusion sequences; Liquid biopsy; Serum marker